Drug utilization evaluation among an elderly population: a retrospective cross‐sectional study in a tertiary care hospital in Pakistan. Issue 2 (13th March 2018) - Saqib, Anum; Atif, Muhammad; Scahill, Shane
Abstract: Objectives: Ageing and its associated physiological changes make elderly more prone to chronic diseases, ultimately leading to escalated drug use. The aim of this study was to execute retrospective drug utilization evaluation among elderly patients discharged from the hospital. Methods: A descriptive, retrospective, cross‐sectional study design was employed. Data were collected from the medical records of discharged elderly patients admitted between July 2016 and December 2016 in Bahawal Victoria Hospital, Bahawalpur, Punjab, Pakistan. Statistical Package for Social Sciences (IBM Corp. Released 2012. IBM SPSS Statistics for Windows, version 21.0. Armonk, NY, USA: IBM Corp.) was used for analysing the data. Multiple linear regression analysis was used to find the independent factors associated with increased utilization of drugs. P ‐value < 0.05 was considered statistically significant. Key findings: The average number of drugs per prescription was 4.74 (SD = 1.4). The most commonly prescribed drug classes were as follows: A – alimentary tract and metabolism (77.8%), J: anti‐infectives for systemic use (68.5) and C: cardiovascular system (67.5%) respectively. The total drug consumption varied between 0.02 defined daily dose (DDD)/1000 patient days and 77.1 DDD/1000 patient days. The maximally consumed drug in all the medical wards was omeprazole. 48.3% patients were prescribed at least one potentially inappropriate medication independent of disease or condition. 10.2% patients were prescribed at least one inappropriate medication dependent on disease or condition. 61.8% prescriptions had drug interactions. The total number of drug interactions found in the prescriptions was 781, and among them, majority (74.2%) were moderate interactions. Conclusions: Our study identified that drug use in elderly is not appropriate and special emphasis must be put on rationalizing the drug use in this population. The findings of this study may provoke the policymakers and healthcare professionals to formulate appropriate strategies for ensuring rational drug use.